AN INVESTIGATION OF STUDENTS’ COMPETENCE IN USING ADJECTIVE PHRASE IN WRITING SKILLS - Abdulhalim Daud; Firmansyah Firmansyah; Sri Ayu Budi Lestari (Tekstual, 2024)
The objective of this study is evaluating students’ competence in using adjective phrases in English writing. The objectives include assessing competence, identifying challenges/errors, and exploring influencing factors. This study applied a mixed-methods approach, combining quantitative questionnaires and qualitative analysis of writing samples, the research unveils varying levels of competence and error patterns. The findings show that students demonstrated a fairly good understanding of adjective phrases, attributive adjectives, and predicative adjectives. However, it was observed that, based on the types of adjective phrases, most students exhibited a better understanding of adjective phrases compared to attributive and predicative adjectives. The results of this analysis provide valuable insights in detailing specific aspects of the curriculum that may need to be strengthened or adjusted to improve student understanding. Overall, an in-depth understanding of the results of the analysis of student performance can provide a solid foundation for the development of more effective learning strategies and better customization of the curriculum according to student needs.